(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Objective: to evaluate the results of treatment of children with impacted ureteral stones using ureterolithotripsy. Material and methods: the treatment results of 73 children aged 5 to 18 years were retrospectively evaluated. The average stone size was 10.0 ± 0.6 mm in length and 5.5 ± 0.7 mm in width. Results: complete stone removal was achieved in 71 patients (97.2%). The total number of intraoperative complications was 24 (33.8%). Conversion from endoscopic intervention to open surgery was required in two cases (2.8%) (Grade III). Ureteral mucosal injury was observed in 6.8% of children (Grade I), and ureteral perforation in 1.4% of cases (Grade II a). Ureteral mucosal burns occurred in 4.1% of patients (Grade II a) during laser lithotripsy. Deformation of the tip of the metal guidewire occurred in 16.4% of cases (Grade I). Postoperative complications were observed in 23 pa-tients (31.5%). Elevated body temperature was noted in 8.2% of cases (Grade I), and hematuria in 9.6% (Grade I). Urinoma (Grade III b) and steinstrasse (Grade II a) were each observed in one child (1.4%). Systemic inflammatory response syn-drome was also reported in one case. Conclusions: Ureteroscopic contact litho-tripsy for impacted ureteral stones in children is an effective and safe treatment method.